Arabica Coffee Plant Response to Atonic Concentration and Production Pruning - Ni Luh Putu Sulis Dewi Damayanti; I Gusti Bagus Udayana; Yohanes Parlindungan Situmeang (SEAS (Sustainable Environment Agricultural Science), 2022)
This study aims to determine the effect of atonic concentration, pruning, and the interaction between atonic concentration and pruning on the growth and yield of arabica coffee plants. This research was conducted at UPP. Catur Paramitha, Catur Village, Kintamani District, Bangli Regency with an altitude of 1250 m above sea level. The experiment lasted for 3 months from September to November 2021. The design used in this study was a Randomized Block Design (RAK) with 2 factors arranged in a factorial manner. The first factor is atonic concentration with 4 levels, namely Ao: 0 ml/l, A1: 1 ml/l, 2ml/l, and 3ml/l while the second factor is pruning which consists of 2 levels, namely, without pruning and with pruning. Observations on the observed variables were carried out every 2 weeks. The variables observed were branch length (cm), number of leaves (strands), number of new shoots (fruit), number of flowers (buds), number of fruit (fruit), and number of the stump (bunch). The results of statistical analysis showed that giving atonic concentrations to coffee plants had a significant to a very significant effect on the variables of number of leaves, number, number of new shoots, number of flowers, and number of fruits, and no significant effect on branch length and number of buds. The pruning treatment showed a very significant effect on all observed variables except for the variable length of branches and the number of buds which showed no significant effect. The interaction between the treatment of the effect of atonic concentration and pruning had a significant effect on the number of leaves, a very significant effect on the number of flowers and fruit, and an insignificant effect on the variable length of branches.